1997
DOI: 10.1046/j.1365-2036.1997.121292000.x
|View full text |Cite
|
Sign up to set email alerts
|

One‐day intensified lansoprazole‐quadruple therapy for cure of Helicobacter pylori infection

Abstract: SUMMARYBackground : Peptic ulcer patients need to be treated with antimicrobials to cure Helicobacter pylori infection. Seven-day quadruple therapy is the regimen with the highest cure rates. An ultra-short quadruple therapy was evaluated prospectively. Methods : Forty-six consecutive H. pylori positive patients (33 had proven ulcer disease) were prescribed lansoprazole 30 mg b.d. on days 1-4, and on day 4 they received in addition tripotassium dicitrato bismuthate 120 mg, tetracycline 250 mg and metronidazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
60
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 25 publications
1
60
1
Order By: Relevance
“…4, 6±8, 22 It has been suggested that metronidazole resistance may be overcome by the addition of a proton pump inhibitor (quadruple therapy) with only 1 week of therapy. 21,23,24 We asked whether a twice a day combination of BMT plus the proton pump inhibitor, lansoprazole (b.d. quadruple therapy) would have promise for the treatment of H. pylori infection.…”
Section: Introductionmentioning
confidence: 99%
“…4, 6±8, 22 It has been suggested that metronidazole resistance may be overcome by the addition of a proton pump inhibitor (quadruple therapy) with only 1 week of therapy. 21,23,24 We asked whether a twice a day combination of BMT plus the proton pump inhibitor, lansoprazole (b.d. quadruple therapy) would have promise for the treatment of H. pylori infection.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have found an eradication rate lower than 75% (6,11,59), and values as low as 25 to 45% have also been recently reported (22,24). Thus, prolonged standard triple therapy for up to 2 weeks has been recommended (9,23,34), and in cases of eradication failure, a quadruple therapy with a proton pump inhibitor, bismuth salt, tetracycline, and metronidazole has been advised as a second-line therapy (8,13,44). More recently, sequential therapy (PPI and amoxicillin for 5 days, followed by PPI, clarithromycin, and tinidazole for 5 days) has become very attractive for clinical practice since impressive efficacy was seen (36,73).…”
mentioning
confidence: 99%
“…This provoked studies exploring shorter treatment durations. In the Netherlands, four-day quadruple therapy was found to perform well (rate of cure greater than 90%) in metronidazole-sensitive strains, but less so in metronidazole-resistant strains (10)(11)(12)(13)(14). Studies showed that with quadruple therapy, most cures occur in one to four days.…”
Section: Uringmentioning
confidence: 99%
“…One-day and two-day quadruple therapies have been explored (15)(16)(17)(18), but these extremely short regimens proved to be ineffective, with a cure rate of only 60% to 76%. Metronidazole resistance was an important determinant for failure.…”
Section: Uringmentioning
confidence: 99%